Migratory movements in a disequilibrium macroeconometric model for West Germany - Wolfgang Franz; Ursula Oser; Peter Winker (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1993)
This paper attempts to evaluate economic effects of migration into Germany on the basis of a macroeconometric disequilibrium model. Germany has the advantage of having experience with migratory movements of guestworkers. There was a tremendous infiow of those workers in the sixties as well as an Immigration stop enacted in 1973. Both aspects are discussed in this study. Moreover, in recent years and in the foreseeable future a high inflow from Eastern Europe into Germany is expected. Extending the model until 1995 a Simulation experiment concerning this inflow is carried out, too. The upshot of the econometric exercise is that the effects of immigration on macroeconomic variables is "regime-specific", i.e., they depend on the type of disequilibrium prevailing on the goods and labor market.
Keywords: 330; Arbeitsmigranten; Internationale Wanderung; Ökonometrisches Makromodell; Simulation; Deutschland